2017
DOI: 10.1007/s12079-016-0373-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MT1-MMP proteolytic function and ERK1/2 signalling influences cell migration and invasion through changes in MMP-2 and MMP-9 levels

Abstract: Membrane type-1 matrix metalloproteinase (MT1-MMP, MMP-14) is a unique protease that cleaves extracellular proteins, activates proMMPs, and initiates intracellular signalling. MCF-7 cells are non-invasive and deficient in MT1-MMP, MMP-2, and MMP-9 expression. We created an MCF-7 cell line (C2) that stably produces active MT1-MMP and demonstrated increased ERK1/2 phosphorylation. MAPK inhibition in this cell line showed an inverse relationship in MMP-2 and MMP-9 transcripts where levels of these genes increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…The results of the present study revealed that isofraxidin reduced the expression of p-AKT in A549 cells; therefore, isofraxidin may affect the expression of the Bcl-2 protein family by inhibiting the AKT signaling pathway, leading to the subsequent inhibition of the proliferation of A549 cells and the induction of apoptosis. ERK has been reported to regulate the expression of MMP family-associated proteins, thus affecting cell migration and invasion (29,30). The present study also revealed that isofraxidin reduced the expression of p-ERK in A549 cells, indicating that isofraxidin may inhibit the expression of MMP-2 and MMP-9 proteins by inhibiting the ERK signaling pathway, subsequently inhibiting the migration and invasion of A549 cells.…”
Section: Discussionsupporting
confidence: 66%
“…The results of the present study revealed that isofraxidin reduced the expression of p-AKT in A549 cells; therefore, isofraxidin may affect the expression of the Bcl-2 protein family by inhibiting the AKT signaling pathway, leading to the subsequent inhibition of the proliferation of A549 cells and the induction of apoptosis. ERK has been reported to regulate the expression of MMP family-associated proteins, thus affecting cell migration and invasion (29,30). The present study also revealed that isofraxidin reduced the expression of p-ERK in A549 cells, indicating that isofraxidin may inhibit the expression of MMP-2 and MMP-9 proteins by inhibiting the ERK signaling pathway, subsequently inhibiting the migration and invasion of A549 cells.…”
Section: Discussionsupporting
confidence: 66%
“…Patients receiving catalpol had significantly lower serum levels of colon cancer biomarkers of carbohydrate antigen 19-9 (CA 19-9), carcinoembryonic antigen (CEA), MMP-2, and MMP-9 as compared to the placebo group. The reduction in these biomarkers may indicate that catalpol reduced metastases in colon cancer patients [89]. Adverse effects were significantly fewer that in patients receiving bevacizumab and, in contrast to bevacizumab, there were no fatal adverse effects [80].…”
Section: Effect Of Catalpol In Cancersmentioning
confidence: 98%
“…38 Interestingly, inhibition of furin through expression of its prosegment reduced the invasive phenotype of breast cancer cell lines in vitro, whereas expression of the prosegment of PCSK6 had the inverse effect, pointing at opposing roles of furin and PCSK6 in breast cancer motility and invasiveness. 39 In another in vitro study furin inhibition was used to decrease MMP14 activity in breast cancer cells, which resulted in changed levels of MMP2 and MMP9, 40 indicating a potential link between furin activity, MMP expression and motility in breast cancer cells. Additionally, Scamuffa et al showed that overexpression of the inhibitory prosegment of furin in MDA-MB-231 cells results in impaired processing of the substrates platelet-derived growth factor A (PDGF-A aka PDGF-1) and IGF1R and delayed tumour growth in vivo.…”
Section: Breast Cancermentioning
confidence: 99%